The Implementation of the Brain Rhythm Method in Enhancing the Quality of Quran Memorization - Aziz, Helmi; Mulyani, Dewi; Inten, Dinar Nur; Nur Hakim, Haditsa Qur'ani; Rizqi, Anzilni Ahsani; Az-Zahra, Sabrina Syawalina (STAI Hubbulwathan Duri, 2024)
It is imperative to raise the standard of Quran memorization, particularly in madrasah diniyah where many teachers require capacity building. The purpose of this study is to assess the brain rhythm method's effectiveness, a cognitive learning approach that synchronizes Quranic recitation with specific brainwave patterns to optimize memorization and retention. The study employs a quasi-experimental method with a sample of 72 sixth-grade students from 8 madrasah diniyah in Bandung Regency. Quran memorization tests were used for data collection, assessing accuracy, fluency, and retention over different time intervals. An independent sample t-test study revealed a statistically significant increase in the group utilizing the brain rhythm method's Quran memory quality over the control group, with a significance level of 0.010 (p 0.05). These findings suggest that brain rhythm techniques can enhance learning outcomes in Quran memorization. Practically, Islamic educational institutions could consider incorporating these methods to enhance teaching effectiveness. It would be beneficial to investigate this method's long-term effects and suitability for use in various educational contexts in future research. Additionally, investigating the underlying mechanisms of how brain rhythm synchronization aids memorization could provide deeper insights and potentially lead to further advancements in teaching strategies. This approach may inspire the development of new educational techniques that leverage cognitive science to improve religious education. Moreover, examining the scalability of this method and its integration with modern educational technologies could further enhance its impact. Thus, the brain rhythm method holds significant potential for advancing the field of Islamic education.